The methodological analysis of sediment phosphate research on the coast of Indonesia: a short review - Amri Adnan; Muhammad Irham; Muhammad Rusdi; Ichsan Setiawan; Sayed Abdul Azis (Depik, 2022)
The Atomic Absorption Spectrophotometer method (AAS) and UV-Vis Spectrophotometer method are often used in analyzing elements and compounds in water and sediment. The comparative method of AAS and UV-Vis analysis in sediments in this article is studied to see the accuracy of the equipment used and the efficiency of the resulting analysis. Analysis of the comparative method of phosphate analysis in coastal sediments shows differences and similarities in the use of the two instruments used even though the methods used based on the results of the review do not show significant differences. Methodologically, various types of methods can be carried out to analyze coastal sediment phosphates. The UV-Vis spectrophotometric method is generally more widely used than the AAS method. For a small number of sediment samples, the ASS method is more efficient than the UV-Vis method; however, UV-Vis is more accurate for dissolved samples because less phosphate is released when identified than the AAS method. Based on this, the AAS method is more effective in analyzing phosphate sediments in coastal areas than the UV-Vis method, but the UV-Vis method for wet samples is more accurate.Keywords:Coastal SedimentPhosphateSpectrophotometerUV-VisAAS